The Acceptance And Nutritional Content Of Soft Cookies Added To Katuk Leaves And Almond Nuts As An Alternative For Snacks That Promote Breast Milk - Khotimah, Ummul; Rita Ismawati (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Breastfeeding mothers need extra nutrients to support breast milk production. One of the efforts to help breastfeeding mothers increase breast milk production is to develop a functional product containing lactogogues. This study involved creating soft cookies with addition of katuk leaves and almonds. The purpose of this study was to determine the effect of the addition katuk leaves and almonds on the acceptability and nutritional content (protein, carbohydrates, fat, and iron) of these cookies as an alternative snack to rise breast milk production. This research method uses a pure experimental method with a completely randomized design. Organoleptic testing was conducted with 5 limited panelists and 25 moderately-trained panelists. Data analysis used non-parametric kruskal wallis test statistics, and if significant differences were found, further analysis was performed using the mann whitney test. The result showed that the addition of katuk leaves and almonds affected the level of liking for color, aroma, and taste and had no effect on texture. The highest average value of liking for color, aroma, and taste was obtained in formula F1 and texture was obtained in formula F2. Determination of the best product using the de garmo method and results obtained that formula F1 is the best formula. The nutritional content analysis of the best product formula 2,5% katuk leaves : 7,5% almonds showed the following per 100 grams: energy of 427.62 kcal, fat of 6.34 grams, protein of 18.6 grams, carbohydrates of 62 grams, and iron of 2.73 mg. Further research is needed to modify the amount of added ingredients to improve the panelists’ liking for the product and to evaluate its impact on the breast milk production.